Die bou van die Suidwestelyn, 1895-1897, en die Nzasm-stasiegeboue op Krugersdorp en Klerksdorp - C.F.R. Zietsman (Contree, 2024)
The Nederlandsch Zuid-Afrikaansche Spoorweg-Maatschappij (NZASM) was established in 1887 with the exclusive purpose of linking the Transvaal Republic by rail with Delagoa Bay. Owing to a number of problems the construction of the so-called Randtram between Springs and Krugersdorp was tackled first. In 1893 the First Volksraad approved the railway between Krugersdorp and Klerksdorp, although it was clear right from the beginning that this line would not pay. However, after the discovery of gold near Klerksdorp and because of the alleged production potential of the Potchefstroom district and the desire to include the old Republican capital (Potchefstroom) in the Transvaal railway system, the construction of the Suidwestelyn (South-western line) went on. Construction had started during July 1895 and on 3 August 1897 the line was open for traffic. The old NZASM station buildings at Krugersdorp and Klerksdorp are still standing and, as they are two of the few elegant station buildings erected by the NZASM, should be preserved as symbols of the Suidwestelyn.